European countries with small populations can obtain low prices for drugs: Lithuania as a case history. (June 2011) - Garuoliene, Kristina; Godman, Brian; Gulbinovičč, Jolanta; Wettermark, Bjöörn; Haycox, Alan
Objectives: Assess whether European countries with smaller populations can obtain appreciable discounts for generics, similar to some of the larger European countries, to investigate the validity of recently published hypotheses.Methods: Observational study involving all 3.4 million ambulatory care patients currently contained within the compulsory health insurance system in Lithuania among four drug classes, with a particular focus on generics. Utilization measured in defined daily doses (DDDs). Prices in terms of reimbursed expenditure/DDD. Reductions in reimbursed expenditure/DDD for generic proton pump inhibitors, statins, angiotensin-converting enzyme inhibitors and selective serotonin reuptake inhibitors in either 2007 or 2009 were compared with 2000 or 2001 originator prices, as well as a range of European countries.Results: There was an appreciable reduction in reimbursed expenditure/DDD for generics in each drug class in Lithuania, such as 56% reduction for generic omeprazole, 65% for generic ramipril, 83% for generic simvastatin, 85% for generic sertraline and 87% for generic atorvastatin. This is despite appreciably lower utilization of proton pump inhibitors, statins and antidepressants in Lithuania versus Western European countries. Reductions in generic prices were similar to those among a range of European countries, with no apparent correlation between the number of competitors and price reductions in practice.Conclusion: European countries with smaller populations can obtain substantial reductions in prices of generics versus originators. This was seen in Lithuania among classes with currently limited utilization versus Western European countries, as well as those with similar utilization patterns. In addition, matching price reductions for generics were seen among Western European countries. Overall, our findings demonstrate that it is possible for European countries with smaller populations to engineer low prices with manufacturers.